Surgical treatment of tetralogy of Fallot with pulmonary valve preservation and transannular patch (comparative analysis) - O. S. Borodinova; R. I. Sekelyk; N. M. Rudenko; I. M. Yemets (Ukrainian Journal of Cardiovascular Surgery, 2018)
There are many methods used for surgical treatment of Tetralogy of Fallot. In view of the differences in the surgical results and conclusions regarding the optimality of these methods used for surgical treatment of Tetralogy of Fallot, we analyzed our experience in managing of such patients.The purpose – is to compare the immediate and short-term results of surgical repair of Tetralogy of Fallot using different techniques. Material and methods. The immediate and short-term results of Tetralogy of Fallot repair with the preservation of the pulmonary artery valve (41 patients) and transannular plasty (14 patients).Results and discussion. It was found that the size and pulmonary artery valve anatomy, the mortality and frequency of reoperations did not differ significantly in two groups. A significant difference was found in the development of residual obstruction of the right ventricular tract and severe pulmonary valve insufficiency in compared groups (22% vs. 0% and 0% vs. 57%; p <0.05).Conclusions. Surgical repair of Tetralogy of Fallot with pulmonary valve preservation is a safe option. To improve the results of Tetralogy of Fallot correction and to avoid reoperations due to residual obstruction of the right ventricular tract, it should be defined pre- and intraoperative echocardiography criteria for choosing the most optimal method of correction.